The position of language used in blogs in the overall scheme of current Lithuanian usage - Miliūnaitė, Rita (Lietuvių kalba, 2008)
Lithuanian blogs appeared ca. in the year 2000, whereas the first blogs have been in operation on the worldwide web since ca. 1994. However, the Lithuanian language used in the blogs has hardly been researched. It is obvious that in terms of quantity and quality it is a new phenomenon and it clearly influences public usage of the Lithuanian language. It would therefore be interesting to investigate its peculiarities. The article aims at analysing the most characteristic linguistic features of records randomly selected from more than one hundred of Lithuanian blogs, to define the position of blogs as a genre of electronic texts in current Lithuanian language usage and to show possibilities of their sociolinguistic research. The paper describes peculiarities of the language of the blogs. The key features include information about the author/s, purpose, content and format, and writing circumstances. The language used in blogs is compared with the language of other genres of electronic discourse, which refers to texts of interactive communication in an electronic medium such as comments on discussions on the web, text messages (SMS), instant messages, etc. The investigation concludes that the language used in blogs is more organised, i.e. their graphic and linguistic expression is similar to journalistic style rather than spoken language, the ideas are presented coherently and consistently, the text is better structured (might also be edited by author), more adapted to language standards familiar to a greater number of readers and has more linguistic self-control. The language used in blogs is not related to any region (thus it cannot be treated as a dialect) nor to any social or ethnic group (thus it cannot be treated as a sociolect). It is a type of language functioning in the electronic medium, the so-called medialect. In terms of linguistic peculiarities, blogs may be described as a genre of contemporary public unrestricted electronic usage. With a great variety of blogs, their different authors and topics, the content created directly and with no mediators, the language of the internet genre may be regarded as actual usage reflecting new trends and changes in the language. This format is open to multilayer linguistic variations; therefore, it makes a good basis for the sociolinguistic research of actual usage taking into consideration various social factors (the bloggers’ age, gender, social standing, academic background, activities, interests etc.). Translated by Ernestas Lomsargis and Inesa Šeškauskienė